All-Optical Switching Using Cavity Modes in Photonic Crystals Embedded with Hyperbolic Metamaterials - Chang Liu; Dong Wei; Xiaochun Lin; Yaoxian Zheng (Crystals)
Hyperbolic metamaterials (HMMs) are highly anisotropic materials with the unique property of generating electromagnetic modes. Understanding how these materials can be applied to control the propagation of light waves remains a major focus in photonics. In this study, we inserted a finite-size HMM rod into the point defect of two-dimensional photonic crystals (PhCs) and investigated the unique cavity modes of this hybrid system. The HMM enhances the efficiency of the cavity system in controlling light transmission. Numerical results demonstrate that the cavity modes based on HMMs can be categorized into various types, showing high Q-factors and promising potential for resonant modulation. Furthermore, the switching performance of the cavity with an HMM rod was examined, revealing that the finite-size HMM modes are highly frequency-sensitive and suitable for nonlinear controlled all-optical switching. These switches, characterized by low power consumption and high extinction ratios, are highly suitable for integration into photonic systems. Our investigation on the new type of HMM cavity illustrates that anisotropic materials can be effectively applied in cavity systems to generate highly efficient modes for filtering and switching.